Dispatch the Shia-Ismaili advocates to the Islamic Maghreb and established the Fatimid state - Asad, Abdulbari; Ismail, Farsat (Humanities Journal of University of Zakho, 2021)
The Ismailia da'wa relied on a network of preachers (da'is) to spread their beliefs in the Islamic world, the da'is were chosen on the basis of their competence, knowledge and intelligence, they were distributed in various Islamic regions, from its east to western, and they had divided the Islamic world in to 12 island or region, for each island or region (Huja) leader, each Huja has da'is, and a number of loyal men for their case. In this study, we will focus on two areas (Yemen and Maghreb), sent to them dais and practiced their activities, and they were able to establish the army and succeeded in using it against the local rulers, and they controlled large areas. American-English orientalist Bernard Lewis (1916-2018) believed that after the success of the Ismailis in subduing the cities, it pushed The Mahdi to emerge.